2004
DOI: 10.1097/01.alc.0000141817.15993.98
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Chronic: Two Distinct Forms of Ethanol Tolerance in Drosophila

Abstract: Flies, like mammals, develop tolerance in response to different ethanol-exposure regimens, and this tolerance affects both the onset of and the recovery from acute intoxication. Two forms of tolerance, rapid and chronic, are mechanistically distinct, because they can be dissociated genetically and pharmacologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 37 publications
2
107
0
Order By: Relevance
“…Observations are limited to 60 min to avoid the effects of rapid tolerance buildup [22][23][24] . The w 1118 mutants display significantly reduced LoRR sensitivity in response to ethanol vapor than does Canton-S (ANOVA between subjects F 1,10 = 57.12, p<0.001, N = 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Observations are limited to 60 min to avoid the effects of rapid tolerance buildup [22][23][24] . The w 1118 mutants display significantly reduced LoRR sensitivity in response to ethanol vapor than does Canton-S (ANOVA between subjects F 1,10 = 57.12, p<0.001, N = 6).…”
mentioning
confidence: 99%
“…The flies did not reach the 50% sedation mark within the hour as the observations were made under our standard LoRR conditions in order to make a direct comparison possible. Observations beyond the hour are problematic due to the buildup of rapid tolerance [22][23][24] . In this experiment, less than 25% of the flies at either circadian time point were sedated at 40 min, indicating that there is a difference in leading edge sedation sensitivity between these groups.…”
mentioning
confidence: 99%
“…27 Previous work in Drosophila has shown that the development of chronic tolerance is blocked by cyclohexamide treatment, suggesting that it requires protein synthesis. 30 Our observation of reduced expression from the associated haplotype suggests that this downregulation of a likely transcriptional repressor may relax the control of expression of downstream loci, facilitating neuroplastic changes in response to ethanol exposure.…”
Section: Discussionmentioning
confidence: 83%
“…The inebriometer has been used most commonly in the past and is the best suited to screening large numbers of mutations. However, it can only measure the knockdown phase of intoxication (Leibovitch et al, 1995;Moore et al, 1998;Singh and Heberlein, 2000;Berger et al, 2004). As has been demonstrated with other assays, flies become hyperactive when exposed to ethanol before becoming sedated (Moore et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In its first published study, one of the trial runs showed a significant row effect (Parr et al, 2001). Direct visual observation of the negative geotactic response and postural control has been used by multiple labs, including ours (Berger et al, 2004;Ghezzi et al, 2004;Wen et al, 2005;Cowmeadow et al, 2005). While this is certainly a thorough way to quantify sedation, it is also labor-intensive and therefore not well suited to the large volume of measurements inherent in a genetic screen.…”
Section: Introductionmentioning
confidence: 99%